2021
DOI: 10.1002/jat.4276
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals exposure is associated with early liver dysfunction among rural residents aged 40–75 years in southwest China

Abstract: Heavy metals exposure has been associated with liver dysfunction in recent reports, while the hepatoxicity of lead (Pb) and cadmium (Cd) has been well established.However, the combined effects of multi-metal in real-world scenario on liver dysfunction are still unclear. This cross-sectional study examined associations between 10 biomarkers of early liver injury and multiple heavy metals levels. The levels of heavy metals/metalloid (magnesium [Mg], calcium [Ca], iron [Fe], zinc [Zn], arsenic [As], Cd, copper [C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The liver is one of the main target organs of arsenic poisoning [ 6 ]. Previous studies have shown that chronic arsenic exposure can cause liver injury, hepatitis, liver fibrosis, cirrhosis, liver cancer, and other related malignant diseases [ 7 , 8 ]. Population epidemiological investigations and experimental studies have confirmed that arsenic can cause liver damage.…”
Section: Introductionmentioning
confidence: 99%
“…The liver is one of the main target organs of arsenic poisoning [ 6 ]. Previous studies have shown that chronic arsenic exposure can cause liver injury, hepatitis, liver fibrosis, cirrhosis, liver cancer, and other related malignant diseases [ 7 , 8 ]. Population epidemiological investigations and experimental studies have confirmed that arsenic can cause liver damage.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their persistent nature, high toxicity, bioavailability in the open environment, and the potential for greater bioaccumulation and biomagnification have posed severe health risks to humans, animals, and plants [7]. For instance, lead (Pb) can adversely affect the human central nervous system (CNS); can cause abdominal pain, irritability, sleeplessness, and headache; and can cause behavioral abnormalities and learning issues in children under the age of five due to higher susceptibility [8]. A higher concentration of zinc (Zn) may cause infertility, CNS disorder, and kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…These multiple route exposu (inhalation, dermal absorption, and direct ingestion) data are necessary to thoroughly sess the dumpsite's deleterious impacts on human health. Moreover, the contaminati of the soil-plant continuum with heavy metals such as Cr, Ni, Fe, Pb, and Zn has also be in focus in recent studies [7][8][9][10][11][12]. Taking these problems into consideration and to find o a sustainable solution in the form of screening various plant species to act as hyperacc mulators for different heavy metals, the current study was conducted to screen hyper cumulator plants growing around the solid waste dumpsite of Peshawar and to ass HM concentrations in the dumpsite's soil and plants and their associated risks to hum health.…”
Section: Introductionmentioning
confidence: 99%
“…Based on urinary Zn levels, we have two hypotheses. One is Zn deficiency ( 55 ): the absorption of Fe in the body also inhibits the absorption of Zn, and the content of Zn excreted in urine increases. In addition, the study population was over 60 years old, and the reduction of Fe accumulation and Zn absorption due to aging may be associated with HUA risk ( 56 ).…”
Section: Discussionmentioning
confidence: 99%